A web-based approach to measure skill mismatches and skills profiles for a developing country the case of Colombia - Cárdenas Rubio, Jeisson (SciELO - Editorial Universidad del Rosario, 2020)
Despite information failures in the labour market and their consequences on unemployment and informality rates, countries like Colombia lack a proper labour market information system to identify skill mismatches and employer skill requirements. The use of online job portals as a potential source of labour market information has gained the attention of researchers and policymakers since these portals can provide quick and relatively low-cost data collection. However, debates continue about the efficacy and robustness of job portals for labour market analysis. Accordingly, this book implements a novel mixed methods approach (e.g. web scraping, text mining, machine learning, etc.) in order to investigate to what extent a web-based model of skill mismatches can be developed for Colombia. This book contributes to our current understanding of the topic by developing a conceptual and methodological approach to identify skills, occupations, and skill mismatches using online job advertisements, which would otherwise be too complex to analyse via other means.